2013
DOI: 10.1074/jbc.m113.507202
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Functional Overlapping and Differentiation among Myosin V Motors

Abstract: Background: MyoVs are molecular motors widely distributed in eukaryotic cells responsible for membrane trafficking and intracellular transport. Results: The cargo-binding domain from human MyoV paralogs was structurally and biophysically characterized. Conclusion: We identified singular structural changes and molecular events conferring functional differentiation and modulating cargo binding. Significance: This work provides structural insights into cargo recognition and regulatory mechanisms in MyoVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 68 publications
(68 reference statements)
1
47
0
Order By: Relevance
“…Several Myo-V isoforms has been reported (Nascimento et al, 2013) and it has been established that the Myo-Vb is implicated in the basolateral trafficking of voltage-gated K + channel Kv1.5 (Schumacher-Bass et al, 2014). Interestingly, Myo-Vc is highly expressed in epithelial (Rodriguez and Cheney, 2002; Jacobs et al, 2009; Nascimento et al, 2013), and this motor protein is known to interact with Rab8 (Jacobs et al, 2009; Xu et al, 2009) which has been reported to play a role in the trafficking of KCa3.1 in epithelial cells (Bertuccio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several Myo-V isoforms has been reported (Nascimento et al, 2013) and it has been established that the Myo-Vb is implicated in the basolateral trafficking of voltage-gated K + channel Kv1.5 (Schumacher-Bass et al, 2014). Interestingly, Myo-Vc is highly expressed in epithelial (Rodriguez and Cheney, 2002; Jacobs et al, 2009; Nascimento et al, 2013), and this motor protein is known to interact with Rab8 (Jacobs et al, 2009; Xu et al, 2009) which has been reported to play a role in the trafficking of KCa3.1 in epithelial cells (Bertuccio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We previously proposed a model of GTD-head interaction by manually docking yeast Myo2p-GTD onto the head of Myo5a. Recently, a similar model was independently proposed by Velvarska and Niessing (17) and by Nascimento et al (16). Here we present the model of GTD-head interaction (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Myo2p and Myo4p) and three types of vertebrate Myo5 (i.e. Myo5a, 5b, and 5c), have been solved (12)(13)(14)(15)(16)(17). The structure of GTD is mainly composed of ␣ helices connected by short and long loops (Fig.…”
mentioning
confidence: 99%
“…A binding surface on Myo4p is provided by the segment extending from 1,325-1,402, where this is structurally adjacent to the N-terminal binding surface, even though is it separated by 264 residues in the sequence. As noted before, the structure of the cargo-binding domain of Myo4p is very different from that of mammalian class V myosins where the latter exist as constitutive dimers and are regulated via a head-tail interaction (18).…”
mentioning
confidence: 99%